2018
DOI: 10.1111/grs.12199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plateau pika disturbance levels on the plant diversity and biomass of an alpine meadow

Abstract: The plateau pika (Ochotona curzoniae) is known to influence the plant diversity and biomass of the alpine meadow, and it is regarded as a pest. The species has been subject to extensive controls without a clear target density in the Qinghai-Tibetan Plateau. We investigated the effects of different plateau pika disturbance levels on plant composition, species diversity and biomass. The density of active burrow entrances was used as an index of disturbance levels I, II, III and IV (corresponding to 8, 19, 27 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…The increased soil BD were mainly attributed to livestock (e.g., yak and Tibetan sheep) trampling, which resulted in mechanical stress imposed on the soils and then induced the collapse of soil structure (Hiltbrunner et al, 2012; Zhou, Gan, Shangguan, & Dong, 2010). In addition, grazing or rodent activities could decrease the amount of aboveground biomass and limit the development of root system, leading to a reduction in SOM inputs (Bai et al, 2015; Pang & Guo, 2018). This was another reason for the increased soil BD because SOM is a loose and porous material that not only serves as the major component of soils (Arvidsson, 1998; Ruehlmann & Körschens, 2009), but also plays an important role in the formation of soil aggregates (Piccolo & Mbagwu, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased soil BD were mainly attributed to livestock (e.g., yak and Tibetan sheep) trampling, which resulted in mechanical stress imposed on the soils and then induced the collapse of soil structure (Hiltbrunner et al, 2012; Zhou, Gan, Shangguan, & Dong, 2010). In addition, grazing or rodent activities could decrease the amount of aboveground biomass and limit the development of root system, leading to a reduction in SOM inputs (Bai et al, 2015; Pang & Guo, 2018). This was another reason for the increased soil BD because SOM is a loose and porous material that not only serves as the major component of soils (Arvidsson, 1998; Ruehlmann & Körschens, 2009), but also plays an important role in the formation of soil aggregates (Piccolo & Mbagwu, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple potential mechanisms responsible for the depletion of SOC and STN stocks after grassland degradation. First, livestock grazing and rodent activities (e.g., burrowing) could negatively impact the growth of plants, reducing both above‐ and belowground productivity of the plant community (Bai et al, 2015; Li, Dong, Wen, et al, 2014; Pang & Guo, 2018). In this case, the inputs of SOM from plants (e.g., plant residues and root exudates) would be decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Plateau pika disturbance in relation to lower palatable plant biomass has also been reported in a previous study (Liu et al, 2017), while prairie dog disturbance has been reported to be related to higher palatable plant biomass (Martínez-Estévez et al, 2013). Prairie dog disturbance encourages the arid grassland in North America to shift from annual plants to perennial plants, in which blue gramma (Bouteluoa gracilis ) and vine mesquite (Panicum obtusum ) are usually perennial plants that are palatable for livestock (Sierra-Corona et al, 2015), whereas plateau pika disturbance enables alpine grassland composition to change from sedge to unpalatable broad-leaved plants in the Qinghai-Tibetan Plateau (Pang & Guo, 2018). In this case, plateau pikas preferentially consume dicotyledons, and most dicotyledons are unpalatable plants (Pang & Guo, 2017;Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As the disturbance intensity increases, the palatable plant biomass, plant species richness, soil organic carbon stock, soil total nitrogen and phosphorus stocks show downward parabolas, demonstrating that there is a threshold of plateau pika disturbance intensity for maximizing the forage availability, biodiversity conservation, carbon sequestration, and soil nitrogen and phosphorus maintenance services. When the disturbance intensity is within the threshold of disturbance intensity, plateau pika disturbance can enhance soil total nitrogen (Li et al, 2014) and organic carbon accumulation (Yu et al, 2017b), increase palatable plant biomass (Pang & Guo, 2018) by improving the growth potential of grass plants (Wang et al, 2012b), and encourage more hygrophytes and mesophytes, annual and perennial, common and rare plants to coexist (Guo et al, 2012b), contributing to higher forage available, biodiversity conservation, carbon sequestration, soil total nitrogen and phosphorus maintenance services. When the disturbance intensity is below the threshold of disturbance intensity, the dominant sedge plants place great competitive pressure on grass plants, which leads grass plants to maintain a low percentage (Pang & Guo, 2018;Wang et al, 2012b) and makes it difficult for rare plants to coexist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation